Production of Fuel Additive Solketal via Catalytic Conversion of Biodiesel-Derived Glycerol - Zahid, I. (American Chemical Society, 2020)
The increase in the synthesis of biodiesel has also contributed to a surplus of crude glycerol, which is a significant bottleneck throughout the supply chain of biodiesel and has produced new problems for its sustainable usage. While there is a broad variety of possible uses of crude glycerol, it is restricted by its purity level, affecting its physical, chemical, and biological properties. In this Review, we look at optimization of the biodiesel production process and significant rise in the use of glycerol. The conversion of impure glycerol into pure glycerol and potential application of glycerol in value-added products are emerging topics. The acetalization of glycerol with acetone in the presence of various heterogeneous catalysts and production of solketal - a valuable green product - are discussed. The research studies described herein mainly focus on innovative and emerging technology for sustainable solketal production, as well as the impact of reaction parameters, removal of water, and catalytic activity in both batch and continuous processes. Globally, the potential prospects for the world market should be determined by the availability and demand for glycerol for use in new industries. This paper illustrates the present scenario for the development of glycerol from the biodiesel sector, the world demand, and future emerging markets for glycerol as a commodity chemical. Â©